Keragaan Kelayakan Usahatani Kemiri (Aleurites moluccana): Studi Kasus pada Petani Kemiri di Desa Labalimut - Abdan Sakuro; Ema Hilma Meilani; Neneng Kartika Rini (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to analyze the feasibility of candlenut (Aleurites moluccana) farming in Labalimut Village, Nagawutung District, Lembata Regency, East Nusa Tenggara Province. The study employed a quantitative descriptive method using a simple random sampling technique involving 36 candlenut farmers as respondents. The feasibility analysis was conducted by calculating revenue, production costs, income, the Revenue-Cost Ratio (R/C Ratio), and the Break-Even Point (BEP). The results showed that the average farmer revenue was IDR 34,601,250, with a total production cost of IDR 3,001,875, resulting in a net income of IDR 31,599,375 per hectare. The R/C ratio of 11.52, which is greater than 1, indicates that candlenut farming is financially feasible and profitable for farmers. Furthermore, the BEP analysis revealed a production break-even point of 100 kg, a price break-even point of IDR 2,603, and a revenue break-even point of IDR 208,021. Based on these findings, candlenut farming in Labalimut Village is considered feasible to operate and has good prospects for increasing farmers' income.